FAKTOR PERSONAL DAN SITUASIONAL PENERIMAAN PESAN DAKWAH - Enung Asmaya (Fakultas Dakwah UIN Prof. K.H. Saifuddin Zuhri, 2016)
The da’wa messages are not necessarily able to subdue mad’u. Subjugation and readiness of mad’u is influenced by personal and situational factors which are always intertwined in giving rulings behavior. Personal factors is surrounding the biological and sociopsychological aspects. Biological aspects such as needs and aspects sociopsychological human basic form of the condition and cognitive, affective and psychomotor of mad’u. The situational factors may include environmental systems, culture, norms, architectural design and the like. Social situation is also part of the reason for mad’u to accept or reject the message of da’wa. Pesan dakwah tidak serta-merta dapat menundukkan mad’u. Penundukan dan kesiapan mad’u dipengaruhi faktor personal dan situasional yang senantiasa berkelindan dalam memberikan putusan-putusan perilaku. Faktorfaktor personal melingkupi aspek biologis dan sosiopsikologis. Aspek biologis berupa kebutuhan-kebutuhan dasar manusia dan aspek sosiopsikologis berupa kondisi dan kemampuan kognitif, afeksi dan konasi mad’u. Adapun faktor situasional dapat berupa sistem lingkungan, budaya, norma, design arsitektur dan sejenisnya. Kondisi sosial juga menjadi alasan mad’u dalam menerima atau menolak pesan dakwah.